MOBILE‐izing Adolescent Sexual and Reproductive Health Care: A Pilot Study Using a Mobile Health Unit in Chicago. (4th February 2018) - Stefansson, Lilja S.; Webb, M. Elizabeth; Hebert, Luciana E.; Masinter, Lisa; Gilliam, Melissa L.
ABSTRACT: BACKGROUND: Adolescents experience numerous barriers to obtaining sexual and reproductive health care (SRHC). Mobile Health Units (MHUs) can remove some barriers by traveling to the community. This pilot study developed Mobile SRHC through an iterative process on an existing MHU and evaluated it among adolescents and providers. METHODS: Mobile SRHC was developed through a mixed‐method, multiphase study. Three key informant interviews with MHU providers, an adolescent needs assessment survey, and a Youth Model Development Session informed model development. Emergency contraception (EC), oral contraceptive pills (OCPs), and depot‐medroxyprogesterone acetate (DMPA) were sequentially incorporated into MHU services. Administrative data assessed method distribution and surveys assessed patient satisfaction. RESULTS: Key informants held positive attitudes toward implementing Mobile SRHC into their practice. Needs assessment surveys (N = 103) indicated a majority was interested in learning about sexual health (66.0%) and obtaining birth control (54.4%) on an MHU. Over 3 months, 123 adolescents participated in Mobile SRHC. Seven packs and 9 prescriptions of EC, 8 3‐month packs and 10 prescriptions of OCPs, and 5 injections and 5 prescriptions of DMPA were distributed. Ninety‐two percent of adolescent participants reported they would recommend Mobile SRHC to friends. CONCLUSIONS: Mobile SRHC is a feasible approach for reproductive health care among adolescents.